Endocrinology adult and pediatric : the adrenal gland - DeGroot, Leslie J.; Jameson, J. Larry; Grossman, Ashley (Philadelphia : Saunders/Elsevier, 2010)
Brought to you by the same expert endocrinologists responsible for the highly acclaimed two-volume Endocrinology clinical reference, Endocrinology: Adult and Pediatric: The Adrenal Gland is a new book that puts all of the latest advances in management of adrenal disorders at your fingertips. Stay abreast of the newest knowledge and advances in adrenal disease, including the molecular genetics of pheochromocytomas and paragangliomas; the newest therapies for adrenocortical carcinoma, written by the organizers of the first major international trials; a survey of adrenal imaging, authored by the world's major diagnostic imaging specialist on cross-sectional CT and MR scanning of the adrenal gland; a comprehensive survey of adrenarche and the adrenopause - topics not adequately covered in most other adrenal endocrinology books; and much more.Count on all the authority that has made Endocrinology, 6th Edition, edited by Drs. Jameson and DeGroot, the go-to clinical reference for endocrinologists worldwide.
The principles, enzymes, and pathways of human steroidogenesis -- Glucocortocoid action : physiology -- Glucocorticoid receptors : their mechanisms of action and glucocorticoid resistance -- Aldosterone : secretion and action -- Glucocorticoid therapy -- Adrenal insufficiency -- Adrenal causes of hypercortisolism -- Defects of adrenal steroidogenesis -- Adrenarche and adrenopause -- Adrenal gland imaging -- Adrenocortical carcinoma -- Primary mineralcorticoid excess syndromes and hypertension -- Mineralocorticoid deficiency -- Pheochromocytoma -- Adrenal surgery -- Cushing's syndrome.
Includes bibliographical references and index.
Keywords: Endocrine glands -- Diseases; Endocrinology; Endocrinology; Adrenal glands